2015
DOI: 10.1126/science.aad2983
|View full text |Cite
|
Sign up to set email alerts
|

The Papaver rhoeas S determinants confer self-incompatibility to Arabidopsis thaliana in planta

Abstract: Self-incompatibility (SI) is a major genetically controlled system used to prevent inbreeding in higher plants. S determinants regulate allele-specific rejection of "self" pollen by the pistil. SI is an important model system for cell-to-cell recognition and signaling and could be potentially useful for first-generation (F1) hybrid breeding. To date, the transfer of S determinants has used the complementation of orthologs to "restore" SI in close relatives. We expressed the Papaver rhoeas S determinants PrsS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…This hypothesis was tested recently by transferring the P. rhoeas SI system to Arabidopsis. Lin et al (2015) showed that expressing Prs-S 1 in Arabidopsis papillar cells and Prp-S 1 in pollen (i.e. an incompatible Prs-S/Prp-S pair) results in SI (Lin et al, 2015).…”
Section: Si Mechanisms: Brassicaceaementioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was tested recently by transferring the P. rhoeas SI system to Arabidopsis. Lin et al (2015) showed that expressing Prs-S 1 in Arabidopsis papillar cells and Prp-S 1 in pollen (i.e. an incompatible Prs-S/Prp-S pair) results in SI (Lin et al, 2015).…”
Section: Si Mechanisms: Brassicaceaementioning
confidence: 99%
“…Lin et al (2015) showed that expressing Prs-S 1 in Arabidopsis papillar cells and Prp-S 1 in pollen (i.e. an incompatible Prs-S/Prp-S pair) results in SI (Lin et al, 2015). Given the phylogenetic distance between P. rhoeas and Arabidopsis, this exciting result suggests that the Papaver SI system may be used to manipulate compatibility in virtually any species, which has long been a goal of plant biotechnologists (see Advances).…”
Section: Si Mechanisms: Brassicaceaementioning
confidence: 99%
“…Unlike the S-RNase-based systems and the Brassica SSI system, the Papaver S-specificity determinants (PrpS and PrsS) are sufficient for SI function. Lin et al (2015) reported a proof-of-principle experiment in which PrpS and PrsS genes from P. rhoeas were transferred to A. thaliana ( Figure 2C).…”
Section: Si In Hybrid Breeding Schemesmentioning
confidence: 99%
“…The identity of the S-determinants and the physiological SI mechanism are briefly described in Molecular Mechanisms of SI and elsewhere (Wilkins et al, 2014). The dramatic demonstration that appropriate expression of PrsS and PrpS can confer SI on otherwise SC A. thaliana (De Graaf et al, 2012;Lin et al, 2015) formed the basis for the patent titled "Engineering of plants to exhibit self-incompatibility" by Franklin-Tong et al (2010). This was not the first successful transfer of SI genes into A. thaliana, as Nasrallah et al (2002) restored SI in A. thaliana by introducing SI genes from A. lyrata.…”
Section: Patented Applications Of Plant Si Systemsmentioning
confidence: 99%
“…Since SI is a natural outcrossing system, it may be an attractive alternative, but until now a portable SI system seemed out of reach. Now, in a recent paper in Science, Lin et al report successfully transferring the Papaver rhoeas SI system into the distantly related and SC Arabidopsis thaliana, suggesting that this type of SI may work in a wide variety of species [3].…”
mentioning
confidence: 99%